2009
DOI: 10.5032/jae.2009.03100
|View full text |Cite
|
Sign up to set email alerts
|

Job-Related Stress Among Secondary Agricultural Education Teachers: A Comparison Study

Abstract: The study sought to explore and compare the current level of job stress among secondary agriculture teachers in Missouri and North Carolina. The accessible populations consisted of secondary agriculture teachers (n = 252) in Missouri and (n = 118) in North Carolina. Data were collected using the Job Stress Survey (Spielberger & Vagg, 1999). From the findings, it was concluded that agriculture teachers in Missouri and North Carolina are not in an overall state of stress compared with norm data. However, time-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 29 publications
(15 reference statements)
4
25
0
Order By: Relevance
“…The factors which determine dissatisfaction and stress must be addressed taking a professional development approach (Walker et al, 2004). Torres, Lawver, and Lambert (2009) conducted a study on job-related stress and found that hours per week at work was the largest predictor of stress. Agriscience teachers have reported professional development needs in time management as indicated by research identifying problems facing the profession (Myers et al, 2005).…”
Section: Theoretical/conceptual Frameworkmentioning
confidence: 99%
“…The factors which determine dissatisfaction and stress must be addressed taking a professional development approach (Walker et al, 2004). Torres, Lawver, and Lambert (2009) conducted a study on job-related stress and found that hours per week at work was the largest predictor of stress. Agriscience teachers have reported professional development needs in time management as indicated by research identifying problems facing the profession (Myers et al, 2005).…”
Section: Theoretical/conceptual Frameworkmentioning
confidence: 99%
“…Respondents were asked about their ability to "Manage work related stress" and "Balance priorities to make time for career and family/personal life" as examples. The four items of the WLB ability construct were derived from findings in other studies and encompassed work stress, time management, and work-life balance (Boone & Boone, 2007;Crutchfield et al, 2013;Edwards & Briers, 1999;Mundt & Connors, 1999;Murray et al, 2011;Myers et al, 2005;Torres et al, 2009;Walker et al, 2004). WLB achievement ability items were measured on a five-point scale which ranged from 1 "Very Low" to 5 "Very High."…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…Although studies have found that agriculture teachers are not experiencing burnout (Croom, 2003), evidence suggests that they do experience overburdening workloads and stress (Boland, King, Williams, Duncan, & Ricketts, 2010;Boone & Boone, 2007;Edwards & Briers, 1998;Moore & Camp, 1979;Mundt & Connors, 1999;Myers et al, 2005;Newcomb et al, 1987;Talbert, Camp, & Heath-Camp, 1994;Torres et al, 2009). Furthermore, there exists a shortage of qualified teachers and attrition among agriculture teachers (Kantrovich, 2010).…”
Section: Theoretical and Conceptual Frameworkmentioning
confidence: 99%
“…Such workshops could provide coping mechanisms suitable for handling many simultaneous demands such as the many applications and reports due at the end of the school year. Research conducted by Torres, Lawver, and Lambert (2009) support this finding and recommend including topics such as time management and stress reduction during professional development opportunities.…”
Section: Conclusion and Recommendationsmentioning
confidence: 70%
“…Torres, Lawver, and Lambert (2009) Other high stressors identified included completing paperwork/reports, preparing proficiency applications, and preparing degrees. These stressors have been identified in previous studies, which site excessive paperwork, working overtime, meeting deadlines, and not enough personal time as contributing to job stress (Torres, Lawver, and Lambert, 2009;Klassen & Chiu (2010). Based on the findings, it would be beneficial to focus in-service training and other personal development opportunities around these topics.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%